Evaluasi Kesesuaian Penyimpanan Obat Di Gudang Farmasi Rumah Sakit Umum Daerah Dr. Soekardjo Kota Tasikmalaya - Ayu Rahmawati; Edi Suhardiana (Jurnal Anestesi, 2023)
Drug storage is one of the security activities for drugs that have been received. Storage of drugs in pharmacy installations is part of the integrity or feasibility of drugs before they are given to patients. Because errors in drug storage can make the dose or potency of the drug decrease and cause losses to the hospital. This research includes non-experimental research in the form of quantitative descriptive research conducted by observation and interviews related to the process of storing pharmaceutical preparations through an evaluation based on the Minister of Health of the Republic of Indonesia No. 72 of 2016, and the Director General of Binfar in 2010 and analysis of drug storage indicators. The average result of conformity to the Permenkes is 86%, the average is obtained from 70% storage requirements, 100% storage components, 100% storage systems, 80% storage methods and 80% storage equipment. The average result of conformity at the Director General of Binfar is 93%, the average is obtained from the spatial arrangement of 100%, preparation of 100% drug stock and 80% storage facilities. And the average results of storage indicators are 40%, with a TOR value of 5,1 times a year, warehouse arrangement is based on FIFO/FEFO, the percentage of expired/damaged drugs is 0.25%, and the percentage of empty drugs is 92%, the percentage of drugs dead by 0.04%. Based on the evaluation of the suitability of drug storage in the Pharmacy Warehouse of RSUD dr. Soekardjo, City of Tasikmalaya, it is necessary to increase the suitability of drug storage.